Morphology of Coronary Ostia in Domestic Shorthair Cat. (30th January 2015) - Barszcz, K.; Kupczyńska, M.; Klećkowska‐Nawrot, J.; Skibniewski, M.; Janczyk, P.
Summary: Diagnosis and treatment of heart diseases due to changes in the coronary vascularization need a detailed knowledge on the morphology and possible variations of the aortic valves and coronary ostia. This study was performed to clarify details on morphology of these structures in domestic cats. The tricuspid aortic valve was examined in 65 domestic shorthair cats. The location of coronary ostia was determined either inferior to (26 and 20%, left and right coronary ostium – LCO and RCO), at (65 and 66%) or superior to the intercommissural line (9 and 14%). In 13 cats (20%), accessory ostia were found either for left, right or both coronary arteries (LCA and RCA). Their position varied between specimens. They were located beyond the main ostium, at its edge, or inside just below the edge. In one cat, no main trunk of the LCA was found. In one cat, two accessory ostia next to the RCO were observed. Coronary ostia in cats show anatomical variants and morphological anomalies. This study provides basic data useful for, for example, angiography performed for diagnosis of cardiac diseases and as a basis for surgical interventions.